INCREASING THE EFFICIENCY OF USING FINANCIAL FUNDS IN BUDGET ORGANIZATIONS - Kalonov Shahijahon Normakhmad ugli (American Journals, 2024)
In this article, the need for effective spending of financial resources in budget organizations and its practical situation were studied using the example of higher education institutions. In particular, the sources of formation of financial funds in higher education institutions and the aspects related to their spending were researched theoretically and practically, and appropriate recommendations and conclusions were formed.
Keywords: Budgetary organizations, financial results, accounting of financial results, international financial reporting, budgetary funds, extra-budgetary funds.